Blood pressure and left ventricular function changes in different ambulatory blood pressure patterns at high altitude. Issue 6 (6th March 2021) - Chen, Renzheng; Yang, Jie; Liu, Chuan; Ke, Jingbin; Gao, Xubin; Yang, Yuanqi; Shen, Yang; Yuan, Fangzhengyuan; He, Chunyan; Cheng, Ran; Lv, Hailin; Zhang, Chen; et al.
Abstract: Acute high‐altitude (HA) exposure induces physiological responses of the heart and blood pressure (BP). However, few studies have investigated the responses associated with dipper and non‐dipper BP patterns. In this prospective study, 72 patients underwent echocardiography and 24‐h ambulatory BP testing at sea level and HA. Patients were divided into dipper and non‐dipper groups according to BP at sea level. Acute HA exposure elevated 24‐h systolic and diastolic BP and increased BP variability, particularly in the morning. Moreover, acute exposure increased left ventricular torsion, end‐systolic elastance, effective arterial elastance, and untwisting rate, but reduced peak early diastolic velocity/late diastolic velocity and peak early diastolic velocity/early diastolic velocity, implying enhanced left ventricular systolic function but impaired filling. Dippers showed pronounced increases in night‐time BP, while non‐dippers showed significant elevation in day‐time BP, which blunted differences in nocturnal BP fall, and lowest night‐time and evening BP. Dippers had higher global longitudinal strain, torsion, and untwisting rates after acute HA exposure. Variations in night‐time systolic BP correlated with variations in torsion and global longitudinal strain. Our study firstly demonstrates BP and cardiac function variations during acute HA exposure in different BP patterns and BP increases in dippers at night, while non‐dippers showed day‐time increases. Furthermore, enhanced left ventricular torsion and global longitudinal strain are associated with BP changes. Non‐dippers showed poor cardiac compensatory and maladaptive to acute HA exposure. However, the exact mechanisms involved need further illumination.